Experimental and Numerical Investigation on Seismic Performance of RC Exterior Beam-Column Joints with Slabs - Zhimeng Wang; Jiao Huang; Zhaoqun Chang; Yongjian Lu (Shock and Vibration)
The effect of a cast-in-place slab on the beam-column joint at beam ends in reinforced concrete (RC) structures under earthquake attacks has not been fully understood, and therefore, it is not manifestly addressed to some of the design criteria or specifications. Consequently, the contribution of slab to the seismic resistance of structures is often ignored or just included in an approximate manner. In this study, the experiment of two 1/2-scaled exterior beam-column joints without slabs and three 1/2-scaled joints with slabs under the combination of quasi-static repeated cyclic loading and constant axial force was carried out to investigate the effect of the cast-in-place slab on the seismic performance of exterior beam-column joints. The results show that for specimens EBCJ1 and EBCJ2 without slab, the decline was approximately 5%, while for specimens EBCSJ1 and EBCSJ3, the decline in the load is obvious and approximately more than 10%. For specimen EBCSJ2, which exhibited a slightly different behavior in the hysteresis curves, the maximum carrying capacity reached at the displacement of 70 mm during the first cycle. The cast-in-place slab has different effects on the failure mechanism and load transfer mechanism of the exterior beam-column joint, which depends on the column-beam moment strength ratio in the loading protocol. The slab has a positive effect on the energy dissipation capacity of the joint but has a negative effect on the load carrying capacity. In addition, finite element (FE) analysis of the tested specimens was conducted. The FE numerical models were established based on the construction information and loading conditions from the experiment and then validated by comparing them with the experimental observation.